Acute toxicity of praziquantel to fish Danio rerio and planktonic crustacean Daphnia magna - Zuskova, Eliska; Piackova, Veronika; Valentova, Olga; Zalohova, Klara; Velisek, Josef (Veterinarni medicina, 2022)
This study evaluated the toxicity of the pyrazino isoquinoline anthelmintic praziquantel (PZQ) to the Danio rerio zebrafish and Daphnia magna water flea. The estimated 24 h and 96 h LC50 of PZQ to the zebrafish was 39.9 mg/l and 30.4 mg/l, respectively. The highest 24 h and 96 h non-lethal concentration (LC0) was 21.7 mg/l and 21.2 mg/l, respectively. The mobility inhibition test of the juvenile Daphnia magna revealed a 48 h EC50 of 42.7 mg/l.
Keywords: antiparasitic; 96 h LC50; water flea; zebrafish; bath treatment